Poverty and Social Exclusion in India : Adivasis - Das, Maitreyi Bordia; Kapoor Mehta, Soumya (World Bank, Washington, DC, 2017)
This brief describes the poverty and social exclusion of the tribal groups in India. Tribal groups or Adivasis are considered to be the earliest inhabitants of India. While India is widely considered a success story in terms of growth and poverty reduction, Adivasis in 2004–2005 were twenty years behind the average. Scheduled Tribes are often conflated with Scheduled Castes in the development literature, although they are completely different social categories. Physical remoteness and smaller numbers have gone together with political isolation and low voice in decision making for the Scheduled Tribes. There have been measures to assure defacto autonomy and self-rule to Adivasis, but implementation has been patchy. More discussion of tribal aspirations and problems from their point of view is needed, rather than an examination of such issues through the lens of policy makers, the bureaucracy, or the civil society.